The Influence of Market Orientation, Learning Orientation, Innovation and Competitive Advantage to Improve Marketing Performance - Nurhasanah, Novi; Murwatiningsih, Murwatiningsih (Management Analysis Journal, 2018)
The study is aimed at examining the effect of market orientation, learning orientation, innovation and competitive advantage on marketing performance. Populations in this research are 41 which 3, 4, and 5 star-rated hotels in Semarang City. The numbers of samples in this research are 120 respondents by using purposive sampling technique. Methods of data collection are using documentation and questionnaires. Data analysis is using Structural Equation Modeling (SEM). The result of this research show that companies which apply learning orientation, innovation and competitive advantage can improve marketing performance, but for market orientation has no effect on marketing performance.